IgG-Associated Hypocomplementemia in Neonatal Lupus: A Retrospective Multicenter Study - Sun W; Li Y; Jin X; Liu X; Li H; Bian J; Li L; Hu J; Huo J; Sun Z; Wang H; Li M; et al. (Journal of Inflammation Research, 2025)
Wenqiang Sun,1 Yihui Li,1 Xinyun Jin,1 Xue Liu,1 Huiwen Li,2 Jingtao Bian,1 Lili Li,3 Jinhui Hu,4 Jie Huo,5 Zexi Sun,1 Huawei Wang,1 Mengzhao Li,6 Changchang Fu,7 Xueping Zhu1 1Department of Neonatology, Children’s Hospital of Soochow University, Suzhou, People’s Republic of China; 2Department of Nephrology, Children’s Hospital of Soochow University, Suzhou, People’s Republic of China; 3Department of Neonatology, the Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou, People’s Republic of China; 4Department of Neonatology, Huai’an Maternal and Child Health Hospital, Huaian, People’s Republic of China; 5Department of Neonatology, Yangzhou Maternal and Child Health Hospital, Yangzhou, People’s Republic of China; 6Department of Child and Adolescent Healthcare, Children’s Hospital of Soochow University, Suzhou, People’s Republic of China; 7Department of Pediatrics, Xinhua Hospital, Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Wenqiang Sun, Email sunwenqiang123456@126.com Xueping Zhu, Email zhuxueping4637@hotmail.comBackground: Hypocomplementemia, defined as a complement C3 or C4 level below the normal lower limit, is strongly associated with an unfavorable prognosis in patients with autoimmune diseases. This study aimed to explore the clinical features and outcomes of patients with neonatal systemic lupus erythematosus (NLE) with hypocomplementemia.Methods: This retrospective clinical study was conducted across four tertiary hospitals in Eastern China on January 1, 2011, and December 31, 2023. This study included 91 patients with NLE. Patients were classified into hypocomplementemic and non-hypocomplementemic groups according to their serum C3 and/or C4 levels. Risk factors for the development of hypocomplementemia were explored using univariate/multifactorial analyses, organ involvement, and follow-up outcomes were compared between groups.Results: The number of NLE patients with hypocomplementemia was 36 (39.56%). Hypocomplementemia group had a significantly lower proportion of fish oil supplementation during pregnancy, a higher proportion of cesarean deliveries, mothers with systemic lupus erythematosus, double antibody positivity for anti-SSA and anti-SSB, and higher serum IgG levels. Multivariate analyses showed that maternal allergic diseases, double antibody positivity, and serum IgG levels were risk factors for hypocomplementemia. Baseline IgG levels negatively correlated with complement C3 and C4 levels. NLE Patients with hypocomplementemia are more likely to have thrombocytopenia, hypoproteinemia, or gastrointestinal involvement than those without hypocomplementemia. Systemic application of glucocorticoids was significantly more prevalent in the hypocomplementemia group. Long-term follow-up revealed that allergy-associated disorders were common in patients with NLE and hypocomplementemia, followed by developmental delay, severe infections, attention- deficit hyperactivity disorder, and anxiety/depression, respectively. Log-rank analysis revealed that these patients had significantly higher frequencies of allergic diseases and developmental delays later in life.Conclusion: Maternal allergic diseases, double antibody positivity, and serum IgG levels were associated with the development of hypocomplementemia in children with NLE. Patients with hypocomplementemia-associated NLE typically exhibit a more severe disease course.Keywords: lupus erythematosus, neonate, immunoglobulin G, hypocomplementemia, risk factors, prognosis